Mitigation Methods of Sick Building Syndrome With an Emphasis on Indoor Height Setting - Harida Samudro; Ganjar Samudro; Sarwoko Mangkoedihardjo (Hamadan University of Medical Sciences, 2022)
The condition of the space environment as a result of the interaction of physical, chemical, and biological factors, in a complex way, can have acute and chronic effects on the physical and psychological health of the occupants. This was the incidence of sick building syndrome, and efforts to reduce and eliminate the syndrome were presented in this case study. The aim was to produce healthy indoor quality and sustainable use by its occupants. The methods used minimum Indonesian standards regarding procedures for planning the housing environment in urban areas. The analysis of changes in the indoor volume employed indoor height variables for a particular floor area to apply flexibility to various building layouts. The variability of changes in the pollutant exposure area and indoor air volume was expressed as a relative change. Setting indoor height was a significant determinant for maintaining healthy indoor air quality through diluting air against pollutants. An additional 0.5 m of room height could increase the air volume by 15%-20% greater than the increase in the pollutant area. It was an effective method both at the design and building renovation stages. The physical and thermal mitigation was generally performed at the building use stage. Some of the conducted approaches included air conditioning (AC), electric or manual ventilation, and chemical-phytotechnological mitigation indoors by adding chemicals to space. The methods of indoor depollution during the use of buildings are still necessary using physical and chemical-phytotechnological methods by placing decorative plants.